Neoplasia cerebral en paciente masculino de 54 años de edad - Muñoz Sarmiento, Shirley Carolina (2018)
The present clinical case study was carried out with the purpose of establishing the nursing care plan to improve the health status of the male patient with cerebral neoplasia, for effect the main needs and problems of the patient were identified, an assessment was made of the clinical history, physical exams, medical diagnosis and the health actions that were carried out in the PAE (Process of Nursing Care), likewise the interventions of the NIC or Nursing Interventions Classification of the patient with cerebral neoplasia were analyzed. To achieve the objectives of the study and establish an appropriate assessment, the NANDA, NIC and NOC methods were implemented, in order to have a more accurate diagnosis. Considering the results achieved, it is determined that the Cerebral Neoplasia is a very risky pathology, which is inside the cranial tissues, on the other hand, analyzing the care plan implemented in the patient, to treat the pathology, it was determined that it existed a good treatment to the patient, the respective evaluations and tests were made to the patient, considering the pathology of the case. It must be considered that the nursing care plan allows identifying the main needs and problems that intervene in the health and well-being of the patient, making the clinical history, physical examinations, medical diagnosis and taking them to the planning of the corresponding care, in the same way, the correct implementation of the nursing care process (PAE) is a crucial part and an indispensable guide in the work of care by the nurse.